Appropriate small machinery for the South Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A pamphlet on this topic was published in August 1989 by IRETA (Institute for Research, Extension and TraininginAgriculture) in their Agro-Facts senes (2/89). IRETA Publicatioris USP Alafua Campus PO Private Baa - Apia WESTERN SAMOA